Atypical iliac unicameral bone cyst – An incidental finding in MRI - Sharma, B B; Bhardwaj, Naveen; Aziz, Mir Rizwan; Singh, Shilpa; Virmani, Nitish; Singh, Raushan; Thidwar, Rajdeep (Indian Journal of Case Reports, 2016)
Bone cyst is a simple fluid filled lesion which can be diagnosed at any age and can occur in any bone of the body. These are non cancerous unicameral bone cysts (UBC). These are asymptomatic and usually do not cause any complications. Though common in the long bones but can rarely occur in flat bones. The iliac bone is a rare location for the occurrence and can be found as incidental finding while doing computerized tomography (CT) or magnetic resonance imaging (MRI) studies. There is no expansion of the bone with unicameral bone cysts but in our present case there was expansion making it atypical presentation. We present a 22-year male who underwent MRI for Lumbosacral spine for his vague low backache symptoms. There was incidental finding of bony lesion in left iliac bone which turned out to be simple bone cyst. The study of Lumbosacral spine was unremarkable.